Dispensing Practices in India and United States - Darekar, Avinash; Patel, Isha; Clemons, Marilee; Tan, Xi; Rana, Rajat; Bhatia, Deepak; Chang, Jongwha (Journal of Pharmacy Practice and Community Medicine)
Physician dispensing refers to the legal practice where physicians directly supply their patients with medication bypassing the need for patients to use a community pharmacy to fill their prescription. This practice is common in India where 80% of all physicians are legally allowed to dispense medications. Problems persists because patients are required to purchase any medication deemed necessary by the physician; therefore, conflicts of interest can arise due to financial incentives based on the number of medications the physicians dispense to the patient. Physician dispensing has negatively impacted community pharmacy relationships by taking away their business and forcing them to close. Similar to the United States, dispensing physicians are regulated by the board of pharmacy and are required to be compliant with the same regulations as pharmacies, however inspections are not nearly as often or as strict. Loopholes in the laws allow physicians to find ways around regulations and be noncompliant without sustaining consequences. Regulations, such as those in United States, that prohibit physicians from receiving profits based on the number of medications they dispense should be created in India to reduce conflicts of interest and prevent community pharmacies from going out of business.
Keywords: Dispensing; Schedule K; Pharmacist; Physician; India